Quality service performance model in academic libraries: a case study at research universities (RUs) in Malaysia / Junaida Ismail …[et al.] - Ismail, Junaida; Musa, Aishah; Ladisma @ Awis, Mahadir; Shari, Sharunizam (Research Management Institute, 2011)
This study in particular examines the quality service performance in academic library. The reason for choosing academic libraries at the four (4) Research Universities is because this university has a high merit provides service par excellence. Thus, the implementation of quality service could be a guideline or standards to others. The objectives of this study are i) To determine whether there exists a relationship between the five dimensions and the service performance of the academic libraries at the four (4) Research Universities in Malaysia; ii) To determine the elements in each dimension that contributed to the service performance of the academic libraries at the four (4) Research Universities in Malaysia and Hi) To evaluate the most dominant dimension that influences the service performance in the academic libraries at the four (4) Research Universities in Malaysia. This study will employ the basic SERVQUAL model by Parasuraman (1996). Five determinant of quality service has been pre-identified which are Library as a Place (Tangible), Collections, Access, Reliability and Empathy. The sampling technique that had been used in this research was the Stratified Random Sampling. Total number of respondent involves are 246. A set of questionnaire were developed to collect the data. The findings of this study may give a useful insight to the services performance provided to the user.